Deviation of Phraseological Unit Semantic Stability as a Means of Phraseological Transformation - Mirgalimova, Liliia Marselevna; Arsenteva, Elena Fridrikhovna; Nikulina, Elena Aleksandrovna (International Journal of Criminology and Sociology, 2022)
The article is devoted to discussing transformed phraseological units based on the American government blog materials. The theoretic part of the work touches upon the question of terminology. The authors study the existing approaches to fixedness (stability, irregularity, occasional use, modifications) of phraseological units. We seek to analyze the modified variants of phraseological units, describe mechanisms of transformations, and provide their translations. Special attention is devoted to deviations of semantic stability within the structure of phraseological units and modifications that appear when deviations occur. The analysis of the examples will provide a better understanding of the process which is being discussed. Among the mechanisms that trigger transformations, we distinguish between metonymy, polysemy, and context, making modifications within the principle of semantic fixedness, among them reconsideration of phraseological unit meaning and literalization of meaning. Finally, in terms of semantic fixedness, we will define two possible variants of phraseological units’ transformations.